The Role of Accounting and Household Financial Planning as Future Investment Efforts in an Islamic Perspective: Peran Akuntansi dan Perencanaan Keuangan Rumah Tangga Sebagai Upaya Investasi Masa Depan dalam Perspektif Islam - Tyas, Winda Sukmaning; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2022)
This study was conducted with the aim of knowing how the role of accounting and household financial planning as a future investment effort in an Islamic perspective on families in Beji village, Beji district, Pasuruan district. This research is a type of descriptive qualitative research. Data collection is done by interview, observation, and documentation. Informants in this study consisted of housewives who also worked (by profession), housewives who did not work (not by profession), and lecturers of Al-Islam and Kemuhammadiyahan Umsida. Based on the results of the study, (1) Housewives who became the object of this study had implemented the role of simple accounting in the household as a future investment effort in an Islamic perspective, the informants applied it with self-awareness and was very flexible. In other words, the housewives in this study practiced simple accounting according to their abilities and needs, without any binding stipulations or regulations. (2) Household financial planning has an important role as a future investment effort in the Islamic perspective. Good household financial planning and in accordance with the corridors of Islam is one way to prosper family life in the world and benefit in the hereafter. A prosperous and well-maintained world life will participate in maintaining maqashid sharia in human life, so that humans can easily realize benefits in their lives.